2019
DOI: 10.1039/c9gc03173a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical TEMPO-catalyzed multicomponent C(sp3)–H α-carbamoylation of free cyclic secondary amines

Abstract: The electrochemical α-carbamoylation of free cyclic secondary amines has been realized under an original TEMPO-catalyzed multicomponent coupling.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
(15 reference statements)
0
24
0
Order By: Relevance
“…Furthermore, advances in mediated methods combined with the Shono‐type anodic oxidation: N‐ hydroxyphthalimide, [55] TEMPO, [56] aminoxyl mediators, [57] and electron‐proton transfer mediators [4] are unlocking new potential both for enhanced functional group compatibility, new multi‐component reactions, and allowing anodic oxidation to proceed at lower overpotentials than was previously possible. This will open new layers of reactivity that were previously out of reach.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, advances in mediated methods combined with the Shono‐type anodic oxidation: N‐ hydroxyphthalimide, [55] TEMPO, [56] aminoxyl mediators, [57] and electron‐proton transfer mediators [4] are unlocking new potential both for enhanced functional group compatibility, new multi‐component reactions, and allowing anodic oxidation to proceed at lower overpotentials than was previously possible. This will open new layers of reactivity that were previously out of reach.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most well‐known nitroxide compounds is (2,2,6,6‐tetramethylpiperidin‐1‐yl)oxyl or (2,2,6,6‐tetramethylpiperidin‐1‐yl)oxidanyl (referred to as TEMPO). Previously reported works suggested that TEMPO and its derivatives could be reduced to form an aminoxy anion and oxidized to an oxammonium cation . It was reported that the electron transfer rate constant of TEMPO oxidation could reach a value around 0.1 cm s −1 , which is much faster than other organic redox mediators (<10 −3 cm s −1 ).…”
Section: Organic Redox Shuttles In Lithium‐ion Rfbsmentioning
confidence: 94%
“…Consequently, TEMPO and its related molecules are actually used as p‐doped compounds by ignoring the electrochemical reduction reaction. In aprotic solvents, for example, MeCN, the electrochemical oxidation of TEMPO occurs at 0.65 V versus SCE, that is, 3.94 V versus Li + /Li . Depending on the composition of the electrolyte solution, the standard redox potential of TEMPO could range from 3.4 to 4 V versus Li + /Li.…”
Section: Organic Redox Shuttles In Lithium‐ion Rfbsmentioning
confidence: 99%
“…Upon anodic oxidation, TEMPO forms a cationic species (TEMPO + ) that then reacts with a secondary cyclic amine. 216 a-carbamoylated products were obtained with good to moderate yields. The reaction was performed in an undivided cell, using graphite as the working electrode, Ni as the counter electrode, and tetraethylammonium tetrafluoroborate as the electrolyte.…”
Section: Scheme 89mentioning
confidence: 98%